TINJAUAN YURIDIS EKSISTENSI KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM KETATANEGARAAN INDONESIA - Faharudin, Faharudin; Fitra Ramdhany, Setya (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
The purpose of the research is to find out the Existence of the Indonesian National Police According to the Three Constitutions and Amendments to the 1945 Constitution. And to find out the Existence of the Indonesian National Police according to the Police Law. The type of research used by the author is normative legal research. The Primary Legal Material used is the 1945 Constitution. After the Amendment, the Decree of the People's Consultative Assembly of the Republic of Indonesia, Legislation related to the implementation of regional government on the Function of Regional Heads in the Implementation of Regional Government in accordance with the principles of Democracy. And in this case in the form of books, internet media, articles, and others. The existence of the Republic of Indonesia National Police (Polri) in the Indonesian state system is an important part of the dynamics of the relationship between executive power and law enforcement in a democratic state. After the 1998 reforms, the Polri was institutionally separated from the Indonesian National Armed Forces (TNI) and constitutionally directly under the President as Head of Government. This study aims to examine the position, function, and role of the Indonesian National Police (Polri) within the Indonesian constitutional structure based on the constitution, laws, and constitutional practices. Using a normative-juridical approach and qualitative analysis of laws and official documents, it was found that the Polri holds a strategic position in maintaining public security and order, enforcing the law, and protecting and serving the community. However, its existence also faces challenges in terms of accountability, oversight, and independence from political influence. Restructuring the role of the Indonesian National Police (Polri) within the framework of checks and balances and strengthening external oversight institutions is crucial to ensuring the rule of law and a healthy democracy. In conclusion, the existence of the Indonesian National Police (Polri) must continue to be directed towards strengthening professionalism and integrity so that it can effectively carry out its constitutional duties within the Indonesian constitutional system.